Relationship between Knowledge Level and Food Menu Selection on Perineal Wound Healing Process. - Evi liana wati; Susanti Pratamaningtyas; Ririn Indriani; Dwi Estuning Rahayu (Health Gate, 2026)
The postpartum period after childbirth is a critical time for women, where perineal wounds are common and can cause discomfort and risk of infection. Food choices play an important role in wound healing, however, some mother avoid consuming meat, fish, and eggs, believing that these food can slow down the healing process. In reality, tissue regeneration requires adequate nutrition, especially protein. This study explored the relationship between the level of knowledge of food choices and the duration of perineal wound healing. A quantitative approach using a descriptive correlation design with a cross-sectional method was used. The sample consisted of postpartum women with perineal wounds at Aura Syifa Kediri Hospital who were selected by purposive sampling. Data were collected through questionnaire and direct observation and analyzed using the chi-square test to identify the relationship between food choices and perineal wound healing. The results showed that respondents who consumed food rich in protein, vitamins, and minerals healed faster than those who adhered to dietary restrictions. A significant relationship was found between dietary choices and duration of perineal wound healing. A healthy diet is essential to accelerate perineal wound healing, with adequate protein intake helping tissue regeneration. At the same time, consumption of vitamin C and iron support the healing process and boosts the immune system. Therefore, it is important to increase education on balanced nutrition for postpartum women to prevent complications that May hinder recovery.Keywords : Dietary Choices, Perineal Wound, Postpartum